(untitled) (Papeles, 2024)
The article examines the inequalities of cultural capital among first-year Psychology students at the Congreso University, in San Juan. The research is based on a situated practice and is part of the final integrative work of the University-level Teaching Specialization Program at the National University of San Juan (UNSJ). The study reveals that the cultural capital inequalities that students bring to university have a significant impact on the learning process from the outset and create difficulties in students’ understanding of theoretical content and in the actual implementation of the academic program. The research also highlights the need to adapt pedagogical practices and curricular content to address the cultural diversity of the student body. Consideration of the heterogeneity of students’ cultural capital is crucial for reformulating teaching methodologies on the basis of their individual trajectories and for promoting the effective integration of first-year Psychology students into the academic environment, thus reducing inequality gaps. This perspective underpins a proposal for pedagogical intervention which is currently being reviewed and analyzed by the Management Team and the Student Guidance Service (SOE) of the same University